Marjolin ulcer: a rare clinical entity that every health professional should be informed about: a narrative review - Berna Aksoy; Hasan Mete Aksoy (Discover Oncology)
Abstract Marjolin ulcer is a term used to refer to malignant degeneration of aggressive nature associated with chronic burn scars or chronic wounds most of the time. Marjolin ulcers are more common in men and are usually diagnosed in the 5th decade of life. It usually has a relatively poor prognosis because it is diagnosed late, and the mortality rate is around 20% on the average. It is important for all healthcare professionals who provide wound care to be knowledgeable about this issue. The patients with chronic wounds and long standing scars should be followed-up closely in this regard. Early and effective treatment of burns and chronic wounds is mandatory to prevent this condition. Appropriate follow-up and early biopsy at the time of detection of any suspicious change improve the prognosis and survival of patients as this approach will provide early diagnosis of Marjolin ulcers.